Efeitos de perfurações artificiais no processo de decomposição em Sus Scrofa (L.) e confecção de uma check-list da entomofauna de Diptera visitante, durante inverno e verão, na região sudeste - Moretto, Richard Edgar [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Forensic entomology is the science that uses insects and other arthropods associated with animal carcasses under decomposition, seeking relevant information to the body, such as location, cause or time of death. Among the insects of forensic interest, the flies are usually the first and most abundant to colonize a carcass. This study aimed to analyze what are the patterns of decomposition, for Sus scrofa, according to a execution of artificial body perforations, aimed the correlation whit forensic sciences, since they cause injury and hemorrhage in the tissues, caused mainly by sidearms, or white weapons. Where used a total of six pigs, three for the winter season and three for the summer, in which, for each season, one of the pigs had no perforations (Control), another had an abdominal perforation measuring about 15cm (P1) and a third pig featuring five abdominal perforations (P5), measuring about 3cm each one. For visual analysis of the effect of these perforations in the decomposition process, in each situation, thermal and digital photos were taken daily, as well as special thermal dataloggers (TidBITS) were placed in various parts of carcasses, to measure the average daily temperatures during the decomposition process. Diptera adults where collected daily in this decomposition sites, aiming to get a check-list of the insects of the order Diptera who visited the carcasses in the period of the experiment, for each season, winter and summer. The results reveals that occurs a significant differences between each treatment for each season: the greater is the number of abdominal perforations, greater is the quantity of decaying flies and the speed of attraction to the substrate too, accelerating, therefore, the decomposition process. Regarding the differences between the two seasons, the decomposition is about four times faster in the summer, a fact that can be understood by the amount of flies collected in this station had been infinitely ...

Entomologia forense é a ciência que faz uso de insetos e demais artrópodes associados a carcaças de animais em decomposição, buscando obter informações relevantes sobre local, causa ou tempo de morte. Dentre os insetos de interesse forense, os dípteros em geral são os primeiros a serem atraídos e os mais abundantes a colonizarem uma carcaça em decomposição. O presente estudo teve como objetivo principal analisar quais são os padrões de decomposição, para Sus scrofa, de acordo com um aumento de perfurações corporais artificiais, visando inferir uma possível aplicação do mesmo para as Ciências Forenses, simulando casos letais ocasionados através de injúrias no tecido e hemorragia devido à utilização de armas brancas, por exemplo. Foi utilizado um total de seis porcos, três para a estação de Inverno e três para o Verão, nos quais, para cada estação, um dos porcos não apresentava perfurações (Controle), outro apresentando uma perfuração abdominal medindo cerca de 15cm (P1) e um terceiro porco apresentando cinco perfurações abdominais (P5), com cerca de 3cm cada. Para a análise visual do efeito destas perfurações no processo de decomposição, para cada situação, fotos digitais e térmicas foram tiradas diariamente, dataloggers específicos de temperatura (TidBits) foram colocados em vários pontos das carcaças para mensurar as médias de temperaturas diárias ao longo de todo o processo de decomposição. Dípteros adultos foram coletados diariamente, visando-se obter uma check-list dos insetos desta ordem que visitaram as carcaças durante todo o experimento, para cada uma das duas estações propostas, inverno e verão. Os resultados mostraram que houve diferença significativa entre cada um dos tratamentos dentro de uma única estação, de forma que, quanto maior a quantidade de perfurações, maior foi a quantidade e velocidade de atração de dípteros para a carcaça, acelerando assim o processo...
Keywords: Diptera; Diptero; Mosca-varejeira; Verão; Inverno; Entomologia forense; Biodegradação; Brasil, Sudeste